Question:উৎপাদকে বিশ্লেষণ কর: `x^2 + 13x + 36`
Answer
`x^2 + 13x + 36` `= x^2 + 9x + 4x + 36` `= x(x + 9) + 4(x + 9)` ` = (x + 9) (x + 4)` (Ans)
Question:উৎপাদকে বিশ্লেষণ কর: `x^2 + 13x + 36`
`x^2 + 13x + 36` `= x^2 + 9x + 4x + 36` `= x(x + 9) + 4(x + 9)` ` = (x + 9) (x + 4)` (Ans)
Question:উৎপাদকে বিশ্লেষণ কর: `x^4 + x^2 - 20`
`x^4 + x^2 - 20 = x^4 + 5x^2 - 4x^2 - 20` `= x^2 (x^2 + 5) - 4(x^2 + 5) = (x^2 + 5)(x^2 - 4)` `= (x^2 + 5) (x^2 - 2^2) = (x^2 + 5) (x + 2) (x - 2)` `= (x + 2) (x - 2) (x^2 + 5)` (Ans)
Question:উৎপাদকে বিশ্লেষণ কর: `a^2 - 30a + 216`
`a^2 - 30a + 216` `= a^2 - 18a - 12a + 216` `= a(a - 18) - 12(a - 18)` `= (a - 18) (a - 12)` (Ans)
Question:উৎপাদকে বিশ্লেষণ কর: `x^6y^6 - x^3y^3 - 6`
`x^6y^6 - x^3 y^3 - 6` `= x^6 y^6 - 3x^3 y^3 + 2x^3 y^3 - 6` `= x^3 y^3 (x^3 y^3 - 3) + 2(x^3 y^3 - 3)` `= (x^3 y^3 - 3) (x^3 y^3 + 2)` (Ans)
Question:উৎপাদকে বিশ্লেষণ কর: `a^8 - a^4 - 2`
`a^8 - a^4 - 2` `= a^8 - 2a^4 + a^4 - 2` `= a^4(a^4 - 2) + 1(a^4 - 2)` `= (a^4 - 2) (a^4 + 1)` (Ans)